Linear and Non-Linear Dynamics of Inertial Waves in a Rotating Cylinder with Antiparallel Inclined Ends - Shiryaeva, Mariya; Subbotina, Mariya; Subbotin, Stanislav (Fluid dynamics & materials processing, 2024)
This work is devoted to the experimental study of inertial wave regimes in a non-uniform rotating cylinder with antiparallel inclined ends. In this setting, the cross-section of the cylinder is divided into two regions where the fluid depth increases or decreases with radius. Three different regimes are found: inertial wave attractor, global oscillations (the cavity’s resonant modes) and regime of symmetric reflection of wave beams. In linear wave regimes, a steady single vortex elongated along the rotation axis is generated. The location of the wave’s interaction with the sloping ends determines the vortex position and the vorticity sign. In non-linear regimes several pairs of the triadic resonance subharmonics are detected simultaneously. The instability of triadic resonance is accompanied by the periodic generation of mean vortices drifting in the azimuthal direction. Moreover, the appearance frequency of the vortices is consistent with the low-frequency subharmonic of the triadic resonance. The experimental results shed light on the mechanisms of the inertial wave interaction with zonal flow and may be useful for the development of new methods of mixing.